The development of coordination abilities and biochemical changes in schoolchildren of primary school age at employment choreography. - Glozhyk Irina Zinov'evna; Yavdoshyk Alla Vasil'evna (Kharkov National Pedagogical University, 2011)
The influence of the developed technique to dance on the development of coordination abilities and reflects changes some biochemical parameters, namely, urinary creatinine and inorganic phosphorus in primary school children involved in choreography. In the experiment involved students 8-9 years (boys). Found that classes in choreography improved level of coordination abilities of students and the experimental group demonstrated a positive impact choreography lessons on physical performance of students, because their body is more adapted to physical activity, and puts them at lower power consumption.